Manajemen Pengelolaan Zakat di Bangladesh - Muhammad Maulana Hamzah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2018)
Bangladesh is one of the developing countries in South Asia which has a similar topography as Indonesia. With majority of population is Muslim and aspects of the economy based on agriculture and garment industry, Bangladesh becomes ideal comparison to Indonesia. But poverty remains as national problem there. With potential 90% of Muslim community, utilizing zakat role to alleviate poverty is still limited. Some data from the Social Report, IRTI and related research is analyzed to find contribution of potential zakah in improving social welfare. In addition, a method review is used to analyze collection, management and distribution of zakat in Bangladesh. Hopefully, this paper become a scientific contribution to the methods of zakah management in Indonesia.